EFFECT OF BALANCED SCORECARD ON FIRM VALUE: THE CASE OF QUOTED MANUFACTURING COMPANIES IN INDIA (CAHIERS MAGELLANES-NS, 2024)
Investigating how the Balanced Scorecard (BSC) affects the value of a company is the driving force behind this research. The financial results of 25 businesses listed on the Bombay stock market have provided proof of the same. Production is the main focus of these businesses. Secondary sources provided the data used in this investigation. For the five fiscal years beginning in 2019 and ending in 2023, the company's financial statements serve as the primary data source. In order to provide a summary of the study's variables' behaviour, descriptive statistics have also been computed. Using a multiple regression model, we have evaluated our hypothesis. The meaningful association between the dependent variable (Firm Value) and the independent variables (BSFINP, BSBUSP, BSCUSP, and BSLGRP) may be examined using a regression model. Firms should leverage views to build business value, according to this study's conclusions. Companies with fewer procedures tend to be more valuable and successful than those with many. The results show that businesses should follow BSC's advice as it will boost their value and performance.